Offensive structuring in men's high-level volleyball: analysis of the attack zone - Gustavo De Conti Teixeira Costa; Mariana Pereira Maia; Juliano Capuzzo; Breno Ferreira de Britto Evangelista; Auro Barreiros Freire; Fernanda Grazielle da Silva Azevedo Nora; Mário Hebling Campos; Herbert Ugrinowitsch (Universidade Federal de Santa Catarina, 2016)
The aim of the present study was to analyze the association between variables of the game on the offensive structure from the zone in which attack is performed in high-level Men's volleyball. The sample was composed by 12 teams, with the analysis of 142 games, which totalized 19,545 reception, set and attack actions. Data analyses were run with descriptive statistic and the qui-quadratic test for searching association between the variables. The results showed association between tempo of attack and attack effect, type of attack and attack zone and attack zone and tempo of attack and attack effect. It was concluded that Brazilian teams underuse backcourt attacks, and the offensive structure accomplished through the faster game, which is mainly important on attacks carried out in positions 2, 3 and 4. Furthermore, the reception quality proved to be the precursor factor in the construction of attack. It was also observed that there was no 1st tempo of attacks from the backcourt, indicating that it is necessary to change the type of game, specifically with the increment of the speed of sets conducted by the backcourt.